Ants Discriminate Between Different Hydrocarbon Concentrations - di Mauro, Giuseppe; Perez, Margot; Lorenzi, M. Cristina; Guerrieri, Fernando J.; Millar, Jocelyn G.; d'Ettorre, Patrizia (Frontiers in Ecology and Evolution, 2015)
Social insects typically discriminate nestmates from non-nestmates using colony-specific blends of cuticular hydrocarbons, which may be considered as a chemical label. Within a species, the cuticular profile shows approximately the same qualitative set of compounds, although these differ quantitatively among colonies. Thus, the relative proportions of particular hydrocarbons may be higher in individuals of one colony compared to those of another (conspecific) colony. Social insects must perceive these differences in ratios in order to efficiently recognize non-nestmates. However, little is known about the underlying perceptual mechanisms. Here we investigated whether ants can discriminate between different doses of individual linear or methyl-branched hydrocarbons. We used the ant Camponotus aethiops as our study organism and differential conditioning of the maxilla-labium extension response as the experimental procedure, to test olfactory discrimination between two concentrations of the same compound (one rewarded and the other punished), using large (wide range, 1:100) and small differences (narrow range, 1:10) in hydrocarbon concentrations. Ants discriminated well between wide-range concentrations of the same compound, but showed asymmetric generalization between narrow-range concentrations. These results indicate that a certain differential in hydrocarbon concentration is essential for efficient discrimination.